1999
DOI: 10.1259/bjr.72.859.10624322
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of image reject rates when using film, hard copy computed radiography and soft copy images on picture archiving and communication systems (PACS) workstations.

Abstract: A comparison has been made of the reject rates of plain images for three separate periods when film, computed radiography (CR) and PACS systems were in operation throughout the Hammersmith Hospital, London. There was a statistically significant reduction in the overall percentage reject rate across all examinations from 9.9% to 8.1% when the hospital changed from using a conventional film based system to a CR system. There was a further reduction in the reject rate to 7.3% when the hospital moved to a hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
2
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 10 publications
3
30
2
1
Order By: Relevance
“…The most common reasons for repeat images included position errors, artifacts, and patient movement, and position errors accounted for the highest percentage of repeat images (as shown in Table 3). The results are similar to those found in previous studies [4,5,10,11,14,15] (Table 6), and indicated that position errors were the most common problem of the radiology department. In June 2008, problems caused by "other human errors" increased greatly, mainly because when the radiology department underwent auditing, they found that radiologic technologists did not use DR properly and deleted images intentionally, causing the number of repeat images to increase to 54 (87.1% of the total number of "other human errors" in 2008).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The most common reasons for repeat images included position errors, artifacts, and patient movement, and position errors accounted for the highest percentage of repeat images (as shown in Table 3). The results are similar to those found in previous studies [4,5,10,11,14,15] (Table 6), and indicated that position errors were the most common problem of the radiology department. In June 2008, problems caused by "other human errors" increased greatly, mainly because when the radiology department underwent auditing, they found that radiologic technologists did not use DR properly and deleted images intentionally, causing the number of repeat images to increase to 54 (87.1% of the total number of "other human errors" in 2008).…”
Section: Discussionsupporting
confidence: 91%
“…Some studies have reported that the most common location of repeat images is in the chest, and this was primarily due to the fact that the chest is the most commonly examined body part [10]. Although in this study the chest was not the body area that generated the highest occurrence of repeat images, the occurrence rate was 4.23%.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Positioning errors were included, with wrong positioning as set by Merrill's Atlas. 8 Cutoff or overconed, off center, marker obstructing the site in question and the part in question was not shown.…”
Section: Error Classificationmentioning
confidence: 99%
“…The image can be reproduced indefinitely without losing colour or detail. The exciting concept of a 'film-less' hospital has many benefits for patient care including decreased exposure to radiation, no loss of images and lower rates of rejection [1][2][3] (Table I). Digital imaging may not initially realise cost benefits, 4,5 but advances in technology will rapidly facilitate this.…”
Section: From the Royal Infirmary Of Edinburgh Scotlandmentioning
confidence: 99%